OPTIMALISASI MANAJEMEN WAKTU DENGAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA [OPTIMIZING TIME MANAGEMENT WITH GROUP GUIDANCE TO INCREASE STUDENT LEARNING MOTIVATION] - Putri, Yoan Rachmawati; Nurjannah, N (Journal of Contemporary Islamic Counselling, 2022)
This study aims to describe how the response of students who experienced a decrease in learning motivation through optimizing time management with group guidance. The research method uses qualitative research methods. The data collection techniques used in this study were interviews, observation, and documentation. This research was conducted on four students at MAN 2 Cilegon who experienced a decrease in learning motivation. The results showed that by optimizing time management through group guidance, it could increase the learning motivation of the respondents (students).